2003
DOI: 10.1300/j003v17n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapists in Rural Healthcare: A “Jack of All Trades”

Abstract: Rural areas are often perceived to have limitations in healthcare resources. The literature indicates that shortages of occupational therapy resources exist within rural health areas. This study reports on a survey that was distributed to rehabilitation departments in Nebraska, excluding only the metropolitan areas of Omaha and Lincoln. Forty-four of the ninety-three surveys sent were completed and returned (47.3%). The survey examined the occupational therapy resources available and those diagnoses treated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Rural therapists in other studies have found that the generalist occupational therapy role has led them to see themselves as a 'jack-of-all-trades' 34,35 . However, Bent suggested that rural therapists are actually 'expert generalists' by virtue of the services they offer to a wide client group with varied conditions that require a diverse range of therapeutic skills (p.208) 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Rural therapists in other studies have found that the generalist occupational therapy role has led them to see themselves as a 'jack-of-all-trades' 34,35 . However, Bent suggested that rural therapists are actually 'expert generalists' by virtue of the services they offer to a wide client group with varied conditions that require a diverse range of therapeutic skills (p.208) 6 .…”
Section: Discussionmentioning
confidence: 99%